2016
DOI: 10.3390/molecules21091233
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation of a Novel Polysaccharide from Pseudostellaria heterophylla and Stimulating Glucose Uptake in Cells and Distributing in Rats by Oral

Abstract: Abstract:The semi-refined polysaccharide of Pseudostellaria heterophylla is a complex polysaccharide that exhibits significantly hypoglycemic activities. A novel homogeneous polysaccharide, named as H-1-2, was isolated from the semi-refined polysaccharide. The mean molecular weight of H-1-2 was 1.4 × 10 4 Da and it was only composed of D-glucose monosaccharide. Structure elucidation indicated that H-1-2 contains pyranride, and has the characteristics of the α-iso-head configuration, a non-reducing end (T-), 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…For instance, Zuo et al used the fluorescence FITC labeled squid ink polysaccharide to trace its transportation through the Caco-2 cells monolayer (Zuo et al, 2016). Chen et al reported that 99m Tc-labeled H-1-2 (Pseudostellaria heterophylla polysaccharide) was used for SPECT/CT studies to investigate the distribution of H-1-2 in mice after oral administration (Chen et al, 2016). Lee et al employed a near infrared fluorescent dye Cy5.5 labeled ZnO nanoparticles for near-infrared fluorescence imaging to investigate the behavior and biodistribution of the marker in mice after oral exposure (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zuo et al used the fluorescence FITC labeled squid ink polysaccharide to trace its transportation through the Caco-2 cells monolayer (Zuo et al, 2016). Chen et al reported that 99m Tc-labeled H-1-2 (Pseudostellaria heterophylla polysaccharide) was used for SPECT/CT studies to investigate the distribution of H-1-2 in mice after oral administration (Chen et al, 2016). Lee et al employed a near infrared fluorescent dye Cy5.5 labeled ZnO nanoparticles for near-infrared fluorescence imaging to investigate the behavior and biodistribution of the marker in mice after oral exposure (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…HPGPC equipped with refractive index detector is considered a powerful, effective, and reliable technique to determine the purity and molecular properties of polysaccharides. The HPGPC elution profiles of CPP1, CPP2, and CPP3 had single and symmetrically sharp peaks ( Figure 2 ), which indicated the polysaccharides were homogeneous [ 18 , 19 , 20 ]. Based on the published literature, single and symmetrically sharp peaks can be obtained through HPGPC analysis [ 19 , 20 ], though some of the peaks were not perfect [ 18 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The HPGPC elution profiles of CPP1, CPP2, and CPP3 had single and symmetrically sharp peaks ( Figure 2 ), which indicated the polysaccharides were homogeneous [ 18 , 19 , 20 ]. Based on the published literature, single and symmetrically sharp peaks can be obtained through HPGPC analysis [ 19 , 20 ], though some of the peaks were not perfect [ 18 , 21 ]. Researchers have accepted the results because the polysaccharides were mixtures of various degrees of polymerization, which made them difficult to obtain very homogeneous components.…”
Section: Resultsmentioning
confidence: 99%
“…Here we exploited the potential therapeutic value of the novel identified polysaccharide H-1-2, which was isolated from the traditional Chinese medicine pseudostellaria heterophylla and implicated in improvement of glucose uptake [15], against T2DM with related disease animal model. We first consolidated the previous observations that hypoxia response was activated in T2DM milieu [17] and the corresponding down-regulation of Sirt1.…”
Section: Discussionmentioning
confidence: 99%